Nitrogen Enrichment Regulates the Changes in Soil Aggregate-Associated Bacterial Community: Evidence from a Typical Temperate Forest - Lv, Wenwen; Liu, Yulin; Hai, Xuying; Liao, Yang; Li, Jiwei; Dong, Lingbo; Shangguan, Zhouping; Deng, Lei (Forests, 2024)
The nitrogen (N) enrichment induced by atmospheric N deposition affects both soil physicochemical properties and bacterial communities. However, how N enrichment affects soil aggregate-associated bacterial communities remains largely unclear. In this study, we conducted a two-year N addition experiment (four N levels: 0, 5, 10, and 20 g N m−2 year−1, corresponding to normal N, low N, medium N, and high N, respectively) in a Quercus liaotungensis Koidz–dominated forest. The distribution, nutrient content, and bacterial community composition of the soil aggregates were measured under various N enrichment conditions. N enrichment changed the aggregate distribution, increased the content of nutrients in aggregates, and altered the aggregate-associated bacterial community composition. N enrichment reduced the complexity of the bacterial co-occurrence network and degraded the interactions between bacteria compared with those observed under the normal N level. Aggregate-associated bacterial community was determined to be primarily affected by N enrichment level but not by aggregate size. The litter properties are the key factors affecting the composition of bacteria in aggregates. These findings improve our understanding of aggregate-associated bacterial responses to N enrichment and the related influencing factors.